Zakażenia grzybicze narządu wzroku – współczesne leki przeciwgrzybicze - Samsel, Agnieszka; Meszaros, Jadwiga (Klinika Oczna / Acta Ophthalmologica Polonica, 2002)
Antifungal agents used in ocular infections are presented. The most common etiology of fungal infections is described. Mechanisms and range of action, available drugs and the latest groups of antifungal agents during clinical trials are presented.